In vitro maturation of oocytes with special reference to goat: a review - Rahman, A.N.M.A.; Abdullah, Ramli; Wan Embong, Wan Khadijah (Asian Network for Scientific Information, 2011)
Oocyte in vitro maturation (IVM) is an Assisted Reproductive Technology (ART) that enables mature oocytes to be generated ex vivo. In vitro production (IVP) of embryos is currently the central focus in livestock industry including goat industry. For any successful IVP program in goat and other livestock, artificial removal of cumulus-oocyte complexes (COCs) from antral follicles and culturing them in essentially standard cell culture conditions or IVM until the maturity is a primary requirement. Therefore, it is very important two know what changes really occur to goat oocytes during IVM. As with in vivo, goat oocytes must undergo both nuclear and ooplasmic maturation for normal fertilization and embryonic development when cultured in vitro. Various locally produced factors work as co-regulators of folliculogenesis and oocyte nuclear and ooplasmic maturation in addition to extrinsic regulation by gonadotrophins and metabolic hormones. Cumulus cells (CCs) surrounding the oocyte play an important role in IVM. The morphology of the cumulus investment is commonly used as selection criteria prior to IVM which greatly influence to the maturity of goat oocytes. Embryo development is also influenced by the events occurring during oocyte maturation. Therefore, it is essential to know those events occurring during goat oocyte maturation in vitro. Various factors such as follicle size; follicular fluid or cells; hormones, serum, growth factors or vitamins in the IVM medium, age of the donor goat and the culture conditions are involved for successful IVM of goat oocytes. The current review describes the criteria and factors affecting maturation of goat oocytes in vitro. © 2011 Asian Network for Scientific Information.